Racial disparities in access to health care infrastructure across US counties: A geographic information systems analysis - Guo, Jingchuan; Dickson, Sean; Berenbrok, Lucas A.; Tang, Shangbin; Essien, Utibe R.; Hernandez, Inmaculada (Frontiers in Public Health, 2023)
Infrastructure system in the U.S. have been shown to be linked to social and health inequities. We calculated driving distance to the closest health care facility for a representative sample of the U.S. population using ArcGIS Network Analyst and a national transportation dataset, and identified areas where Black residents have a longer driving distance to the closest facility than White residents. Our data demonstrated that racial disparities in access to health care facilities presented large geographic variation. Counties with significant racial disparities were concentrated in the Southeast and did not correspond to counties with a greater proportion of the overall population >5 miles to the closest facility, which were concentrated in the Midwest. This geographic variation demonstrates the need to adopt a spatially explicit data driven approach in the design of equitable health care facility establishment that address the specific limitations of the local infrastructure.